DOI: 10.4018/978-1-60566-388-3.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Electronic Government Readiness in Egypt

Abstract: Electronic Government (e-Government) has rapidly become a political imperative at local, national and international level. The drive to implement e-government has become of critical importance globally. The e-government revolution offers the potential to reshape the public sector and remake the relationship between citizens and government. Several developing nations, including Egypt, having witnessed the benefits realized by e-Government in developed countries, took e-Government initiatives and achieved differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 58 publications
2
47
0
Order By: Relevance
“…Interviewees confirmed the findings in the literature that action plans are important to ensure achievement of e-Government milestones and objectives (Bakry, 2004, Azab et al, 2009, World Bank, 2006. For instance, the Assistant Manager of IT Development (Interviewee # 12) confirmed that "the e-Government strategy has an action plan with all important KPIs."…”
Section: A Model For Organizational E-government Readinesssupporting
confidence: 68%
See 2 more Smart Citations
“…Interviewees confirmed the findings in the literature that action plans are important to ensure achievement of e-Government milestones and objectives (Bakry, 2004, Azab et al, 2009, World Bank, 2006. For instance, the Assistant Manager of IT Development (Interviewee # 12) confirmed that "the e-Government strategy has an action plan with all important KPIs."…”
Section: A Model For Organizational E-government Readinesssupporting
confidence: 68%
“…All officials interviewed also confirmed the importance of processes automations in OEGR by applying ICT application systems that manage and integrate the data objects to support the business functions in the Business Architecture (Ebrahim & Irani, 2005b, Azab et al, 2009Lee, 2010a) for example: (Interviewee # 12) confirmed the importance of implementing multiple ICT applications: "The main ICT applications projects implemented at the organization were core business: civil affairs systems ("MGEEM", "SHOMOS", "TAM", Appointment system), passports, traffic, training system, Visa system, and ERP. Interviewees also discussed strategies for reassessing shared application systems and interconnecting them to ensure complete e-Government.…”
Section: Processesmentioning
confidence: 88%
See 1 more Smart Citation
“…In this situation, according to Azab et al (2009), e-government is predicated on leveraging the power of technology to deliver services provided by governments. However, e-government is still in an early stage and has not achieved many of the expected outcomes such as cost savings and downsizing, amongst other issues (Azab et al, 2009). Moreover, according to UNDESA (2003) reports, the e-government projects failure rate reached somewhere between 60-80%.…”
Section: Technological Aspects Of E-government Readiness and The Gapmentioning
confidence: 99%
“…These comprise applications such as hardware, software, communication and networks infrastructure and Internet penetration respectively. Azab et al (2009) developed an e-government appraisal framework encompassing several components such as people, technology, processes, and strategic planning. Technology in this framework comprises information system structure, hardware, as well as technical support and development.…”
Section: Technological Aspects Of E-government Readiness and The Gapmentioning
confidence: 99%